A study on rapid diagnosis (by PCR) and cost-effective treatment of pulmonary mycosis - Kumar, Saurabh; Shaifali, Iram; Chandra, Shalini (International Journal of Research in Medical Sciences, 2018)
Background: Incidence of Pulmonary Mycosis is rampantly growing in critically ill patients. This study was designed to comparatively evaluate conventional and molecular method-Polymerase Chain Reaction (PCR) for detecting Candida and Aspergillus species in Brocho-Alveolar Lavage (BAL) samples and secondarily to find out the Cost-Effective treatment for Pulmonary Mycosis. Methods: In this study 100 BAL-specimens were collected from patients suspected of Pulmonary Mycosis. These samples were examined for Aspergillus and Candida species by preparation of wet smear using potassium hydroxide, Gram staining, Culture media and Polymerase Chain Reaction (PCR). For Cost-Effectiveness analysis(CEA), a decision tree model was constructed for Anidulafungin and Fluconazole The probability of treatment success and mortality rate were extracted from published Randomized Control Trials. Incremental Cost Effectiveness Ratio (ICER) was calculated. Results: Out of 100 samples, 22 were found to be positive for mycotic infections, 9 were detected as Candida and 13 as Aspergillus. On comparing with KOH and Culture, it was observed that all KOH positive and all Culture positive fungal infections were PCR positive. In no cases PCR negative was identified either culture or KOH positive. This establishes the superiority of PCR over conventional diagnostic methods. Anidulafungin was associated with an Incremental Cost Effectiveness Ratio (ICER) of INR 1,13,217 per LY saved, which was below the implicit ICER threshold for India. Conclusions: PCR is a novel molecular method for early and definitive diagnosis of fungal infection and Aidulafungin appears to be the cost-effective drug for treatment of Pulmonary Mycosis.